PENGARUH DISIPLIN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI PADA KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG PEMATANGSIANTAR - Situmeang, Bonar Sahala; Lie, Darwin; Butarbutar, Marisi; Simatupang, Sudung (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2018)
The formulation of this research is how the influence of work discipline and organizational commitment to employee performance at the Kantor Pelayanan Kekayaan Negara dan Lelang Pematangsiantar. The method used in this paper is literature research and field research. Its population is all employees of Kantor Pelayanan Kekayaan Negara dan Lelang Pematangsiantar amounting to 24 people. The data used are qualitative and qualitative data, and data collection techniques used are questionnaire method, interview method and documentation method. Then the technique of data analysis using qualitative descriptive method and quantitative descriptive method.The result of analysis from multiple linear regression is Å¶ = 25,667 + 0,723 X1 + 0,682 X2, means that work discipline and organizational commitment has a positive effect to employee performance. The result of analysis coefficient correlation is r = 0.778 means that there is a moderately high and positive correlation between work discipline and high organizational commitment and employee performance. Then obtained the value of coefficient of determination is 0,606, The level of employee performance can be explaned by work discipline and organizational commitment as big as 60.6%., while 39,4% explained by other factors not discussed in this study. From the results of processing and calculation of the questionnaire, the authors get the conclusion that the leadership style and organizational culture applied by Kantor Pelayanan Kekayaan Negara dan Lelang Pematangsiantar have a positive and significant impact on employee performance. This is proven by hypothesis testing simultaneously, where the test result fhitung (16,124) > ftabel (3,47) with significance level 0,000 < alpha 0,05Â Keywords: Work Discipline, Organizational Commitment and Employee Performance